Understanding science in the service and care of mental health and disorders (2019)
ABSTRACT: Caring for mental health and mental disorders, from primary health attention, is a prime right. The objective of this study was to examine the testimonies of health attention services users regarding the assistance attitudes and practices. This was a hermeneutic qualitative study of several cases. Findings: It can be inferred that there exists a relative crisis in the feeble application of a public policy and in the capacity to encourage meaningful learnings in function of higher or lower potentials, linked to the construction of subjectivities. Conclusions: it is necessary to make a profound reflection on the mutation of meaning and the senses of the service and care of mental health and mental disorders, especially for the re-signification of the patient's human and psychoaffective domains in behalf of the actors involved in providing services from a comprehensive and systematic perspective. This should be encompassed with the pharmaceutical service in the intersectorial team, searching for an alternative cognitive training of the brain, as an endogenous substances generator, to strengthen the balance between the mind-emotions and the organic, in favor of the individual and social well-being, while maintaining the use of psychopharmacological drugs only when strictly necessary.